2018
DOI: 10.3389/fpubh.2018.00293
|View full text |Cite
|
Sign up to set email alerts
|

The Family Check-Up 4 Health (FCU4Health): Applying Implementation Science Frameworks to the Process of Adapting an Evidence-Based Parenting Program for Prevention of Pediatric Obesity and Excess Weight Gain in Primary Care

Abstract: Implementation experts have recently argued for a process of “scaling out” evidence-based interventions, programs, and practices (EBPs) to improve reach to new populations and new service delivery systems. A process of planned adaptation is typically required to integrate EBPs into new service delivery systems and address the needs of targeted populations while simultaneously maintaining fidelity to core components. This process-oriented paper describes the application of an implementation science framework an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 74 publications
1
39
1
Order By: Relevance
“…Participants were 240 children and their primary caregivers enrolled in the Raising Healthy Children project, 33 a randomized trial of the Family Check‐Up 4 Health programme 34 for the prevention of excess weight gain. The programme was delivered in coordination with five paediatric primary care practises in Maricopa County, Arizona.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were 240 children and their primary caregivers enrolled in the Raising Healthy Children project, 33 a randomized trial of the Family Check‐Up 4 Health programme 34 for the prevention of excess weight gain. The programme was delivered in coordination with five paediatric primary care practises in Maricopa County, Arizona.…”
Section: Methodsmentioning
confidence: 99%
“…It therefore needed adapting to Australian standards and services, whilst still being applicable, practical and cost-effective for both service users and clinicians in mental health services (Bauer, Damschroder, Hagedorn, Smith, & Kilbourne, 2015;Smith et al, 2018). Adaptations of evidence-based practices are a commonly used implementation strategy, to ensure that the tool is suitable to the targeted service and population (Smith et al, 2018). There was a need to ensure that multiple disciplines (doctors, nurses, occupational therapists, psychologists and social workers) were able to grasp and utilize the tool effectively, as many case managers in the community mental health settings in Australia are not nurses.…”
Section: Developing the Australian Hipmentioning
confidence: 99%
“…There was a need to ensure that multiple disciplines (doctors, nurses, occupational therapists, psychologists and social workers) were able to grasp and utilize the tool effectively, as many case managers in the community mental health settings in Australia are not nurses. Smith et al (2018)found little evidence that adapting evidence-based practice is detrimental to the effectiveness of the tool, as long as the core components of the tool are maintained.…”
Section: Developing the Australian Hipmentioning
confidence: 99%
“…After 6 months of implementation, we measured general acceptability using the 15-item Evidence-Based Practice Attitudes Scale, which has good internal consistency (α > .75) and validity (Aarons, 2004), and conducted a brief interview (Smith, Montaño, Mauricio, Berkel, & Dishion, 2016). Scores on the Evidence-Based Practice Attitudes Scale (mean = 2.93; out of 4) indicated acceptability (Montaño et al, 2014).…”
Section: Assessing Implementation Processes and Outcomesmentioning
confidence: 99%